Kurikulum Merdeka: Langkah Baru Untuk Masa Depan Pendidikan Indonesia - Sari, Ike Dian Puspita; Pusparini, Indrawati; Rachman, Anita Kurnia (CV SWA Anugerah, 2024)
Kurikulum Merdeka is the latest effort in Indonesian education to produce graduates who are creative and ready to face the future. This curriculum provides flexibility for schools to organize learning according to local conditions. Its implementation at Tunas Bangsa Vocational School Malang faces its own challenges, such as the complexity of the transition process and the need for adequate assistance. The ultimate goal of this effort is to improve the quality of education in schools and prepare teachers to face the challenges of the times through literacy, numeracy and technology adaptation programs.